Mazurka - Armstrong, Campbell (London Coronet Books, Hodder and Stoughton Ltd, 1988)
Scotland Yard detective Frank Pagan returns in this spy thriller by the author of "Jig". Pagan's relatively unimportant job as an escort to a Soviet official becomes a nightmare when the official is assassinated in Edinburgh and Pagan is enmeshed in a plot involving the KGB.
Keywords: Cuba -- Castro, Fidel